BEBERAPA FAKTOR YANG MEMPENG ARUHIMIGRASI TENAGA KERJA INDONESIA (TKI) KE LUAR NEGERI - Waridin, Waridin (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
The difference of economic conditions and job opportunities inter countries can be one of the causes why manpower migration to the socially and economically beneficial countries happens. This research is aimed at analyzing some factors, which effect TKI (Indonesian Man Power) migration to foreign countries. Beside, this study is also aimed at analyzing the migration patterns of Indonesian Man Power to work abroad. The sampling method is carried out with multi stage, namely according to the Job groups power working in target countries. To analyze the factors which effect why Indonesian manpower migrates and works abroad is used "place utility" model or modificated "migration intention". Using logic binary regression and logic multinomial carries out data analysis.The analysis outcome shows that there are five factors which effect why Indonesian manpower migration and works abroad, i.e. marital status, family burden, social, economic, and job experience factor. While other factors, statistically cannot explain how Indonesian man power work and stay abroad. Seen from statistic significance, the main factors which effect the Indonesian manpower intention to work abroad are job experience abroad, the number of income, maritalstatus, the number of family burden, and the length of stay in the target country.